2011
DOI: 10.1007/s12098-011-0427-8
|View full text |Cite
|
Sign up to set email alerts
|

Priority Mental Health Disorders of Children and Adolescents in Primary-care Pediatric Settings in India 2: Diagnosis, Pharmacological Treatment and Referral

Abstract: The advent of pediatric psychopharmacology has enormously improved psychiatric care of children and adolescents. Nonetheless, our practice of diagnosis, treatment and referral in primary-care pediatric settings is not optimum as current evidence based knowledge is not regularly applied in the actual clinical circumstances. To help primary-care pediatricians minimise this in research-clinical practice, pharmacological treatment and referral in their clinical practice, they need to follow a two-tier diagnostic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Rottlerin-treated animals showed significantly reduced MACC1 expression ( p < 0.05), confirming that rottlerin acts as a transcriptional inhibitor of MACC1 and thus inhibits MACC1-induced metastasis formation in vivo. We analyzed further rottlerin-induced effects by determining the mRNA expression levels of genes that can be regulated by rottlerin (CDC20, mTor, and SKP2) [3840]. No significant expression regulation upon treatment with rottlerin was observed (S3 Fig).…”
Section: Resultsmentioning
confidence: 99%
“…Rottlerin-treated animals showed significantly reduced MACC1 expression ( p < 0.05), confirming that rottlerin acts as a transcriptional inhibitor of MACC1 and thus inhibits MACC1-induced metastasis formation in vivo. We analyzed further rottlerin-induced effects by determining the mRNA expression levels of genes that can be regulated by rottlerin (CDC20, mTor, and SKP2) [3840]. No significant expression regulation upon treatment with rottlerin was observed (S3 Fig).…”
Section: Resultsmentioning
confidence: 99%
“…Weight based dosing is commonly used to calculate the necessary dosage for pediatric population as a step down model from evidences available in adult psychopharmacological literature. [1] Pejovic-Milovancevic et al conducted a study on use of psychotropic medication in pediatric inpatients and found that the most commonly prescribed medications were antipsychotics (45.9%), antidepressants (17.2%), mood stabilizers (16.1%), benzodiazepines (14.4%), and other psychotropic drugs (6.4%). Their study also showed that the most frequently prescribed antipsychotic was Risperidone and the most frequently prescribed antidepressant was selective serotonin reuptake inhibitor (SSRI).…”
Section: Sirmentioning
confidence: 99%
“…The advent of pediatric psychopharmacology has enormously improved psychiatric care of children and adolescents;[2] however, there is hesitancy in the use of medication in children. Evidence-based pediatric psychopharmacology is essential for better care and avoiding legal issues.…”
mentioning
confidence: 99%